2019
DOI: 10.1080/15384101.2019.1637201
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin heavy chain phosphorylated at T606 plays a role in proper cell division

Abstract: Clathrin regulates mitotic progression, in addition to membrane trafficking. However, the detailed regulatory mechanisms of clathrin during mitosis remain elusive. Here, we demonstrate novel regulation of clathrin during mitotic phase of the cell cycle. Clathrin heavy chain (CHC) was phosphorylated at T606 by its association partner cyclin G-associated kinase (GAK). This phosphorylation was required for proper cell proliferation and tumor growth of cells implanted into nude mice. Immunofluorescence analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A substrate of GAK phosphorylation is ATP1a3 as demonstrated by chemical genetic identification (Lin et al, 2018) and this is necessary for cargo trafficking. Additionally, GAK has been shown to phosphorylate clathrin heavy chain and AP2 which play a role in vesicle membrane formation and cargo packaging at the cell membrane, respectively, adding further evidence to the role of GAK in the vesicular process (Korolchuk and Banting, 2002;Yabuno et al, 2019). In contrast to DNAJC6/auxilin, GAK is an essential protein during development and adulthood in mice, with GAK knockout being lethal (Lee et al, 2008).…”
Section: Dnajc6 Dnajc13 and Dnajc26mentioning
confidence: 96%
“…A substrate of GAK phosphorylation is ATP1a3 as demonstrated by chemical genetic identification (Lin et al, 2018) and this is necessary for cargo trafficking. Additionally, GAK has been shown to phosphorylate clathrin heavy chain and AP2 which play a role in vesicle membrane formation and cargo packaging at the cell membrane, respectively, adding further evidence to the role of GAK in the vesicular process (Korolchuk and Banting, 2002;Yabuno et al, 2019). In contrast to DNAJC6/auxilin, GAK is an essential protein during development and adulthood in mice, with GAK knockout being lethal (Lee et al, 2008).…”
Section: Dnajc6 Dnajc13 and Dnajc26mentioning
confidence: 96%
“…cyclin G-associated kinase (GAK) is a ubiquitously expressed serine/threonine-protein kinase that primarily localizes to the perinuclear trans-Golgi and the plasma membrane regions (22,23). GAK, which was initially identified as a direct partner of cyclin G (24), has been associated with a diverse range of biological processes, including the maintenance of centrosome maturation and cell cycle progression (25)(26)(27)(28), clathrin-mediated endocytosis (22,23,(29)(30)(31), epidermal growth factor receptor (EGFR) signaling (32) and lysosomal enzyme sorting (33). In addition, GAK has been reported as a binding partner of leucine-rich repeat kinase 2 (LRRK2) (34), which has previously been reported to control autophagy in several systems (35)(36)(37).…”
Section: Targeted Disruption Of Gak Stagnates Autophagic Flux By Disturbing Lysosomal Dynamicsmentioning
confidence: 99%
“…Depletion of CHC by RNAi results in multipolar spindles, and acute inactivation of clathrin by chemically induced dimerization fragments metaphase centrosomes. A more recent study has found that GAK phosphorylates CHC at the T606 site, and the phosphorylated CHC is preferentially localized to centrosomes in interphase as well as in mitosis [62].…”
Section: Mitotic Moonlighting Functions Of Endocytic Proteinsmentioning
confidence: 99%